PERHITUNGAN VALUE AT RISK (VaR) DENGAN SIMULASI MONTE CARLO (STUDI KASUS SAHAM PT. XL ACIATA.Tbk) - Siti Alfiatur Rohmaniah (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2017)
Value at Risk (VaR) can be simply defined as an estimate of the maximum potential loss under the normal market conditions at a specific time period and with the specific confidence level. For the calculation can be done by various methods including VaR parametric estimates. VaR is calculated by simulating the properties of the risk factors and the value of assets by raising the sequence of random asset prices at the T time, given the value of asset prices sample with time t where T> t.